Photocatalytic Degradation of Anthracene in Closed System Reactor - Faiq F. Karam; Falah H. Hussein; Sadiq J. Baqir; Ahmed F. Halbus; Ralf Dillert; Detelf Bahnemann (International Journal of Photoenergy)
Polycyclic aromatic hydrocarbons (PAHs) represent a large class of persistent organic pollutants in an environment of special concern because they have carcinogenic and mutagenic activity. In this paper, we focus on and discuss the effect of different parameters, for instance, initial concentration of Anthracene, temperature, and light intensity, on the degradation rate. These parameters were adjusted at pH 6.8 in the presence of the semiconductor materials (TiO2) as photocatalysts over UV light. The main product of Anthracene photodegradation is 9,10-Anthraquinone which isidentified and compared with the standard compound by GC-MS. Our results indicate that the optimum conditions for the best rate of degradation are 25 ppm concentration of Anthracene, regulating the reaction vessel at 308.15 K and 2.5 mW/cm2 of light intensity at 175 mg/100 mL of titanium dioxide (P25).